Free (ℓr, rr)-dibands - Zhuchok, A.V. (Algebra and Discrete Mathematics, 2013)
We prove that varieties of (ℓr, rr)-dibands and (ℓn, rn)-dibands coincide and describe the structure of free (ℓr, rr)-dibands. We also show that operations of an idempotent dimonoid with left (right) regular bands coincide, construct a new class of dimonoids and for such dimonoids give an example of a semiretraction.